Development and Validation of Stability Indicating RP-HPLC Method for Pyrimethamine, Sulfadoxine, and Artesunate Estimation in Bulk and Its Formulation Applying DOE (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Artesunate (ART) is a prodrug used as an antimalarial agent that acts by malarial proteindamage through alkylation. Pyrimethamine (PYR) is an antiprotozoal agent that acts by interfering with thesynthesis of tetrahydrofolic acid. Sulfadoxine is a dihydropteroate synthetase inhibiter which makes difficultyin parasite reproduction. A stability-indicating high-performance liquid chromatography (HPLC) techniquehas been established for the quantification of PYR, sulfadoxin, and ART applying design of experiment.Material and Methods: The phosphate buffer (pH 3.0):acetonitrile (80: 20) was used as the mobile phase, andhypersil BDS C18 (250 × 4.6 mm; 4 m) column at a flow rate of 1 mL/min was used for the chromatographicseparation. The detection wavelength was set at 237 nm. The mobile phase was optimized using 32 full factorialdesign. Results and Discussion: The optimized method contains the retention times of PYR, sulfadoxin, and ARTat 3.653, 4.920, and 8.310 min, respectively. The method shows a good linearity in the concentration range of0.5–2.5 μg/mL for PYR, 10–50 µg/mL for sulfadoxin, and 4–20 µg/mL for ART. The stability study of the drugswas performed by acid, alkali, oxidation, thermal, and photolytic degradation. Conclusion: The proposed stabilityindicating HPLC method was found to be simple, specific, practical, accurate, quick, and affordable. It wasalso suitable for the routine analysis, quality control, and percentage degradation of pharmaceutical preparationscontaining these drugs either individually or in combination.